2011
DOI: 10.1590/s0100-69162011000100010
|View full text |Cite
|
Sign up to set email alerts
|

Velocidade de semeadura da soja

Abstract: Teve-se o objetivo de estudar a influência da velocidade da semeadura na cultura da soja, com sistemas dosadores de sementes dos tipos disco alveolado horizontal e pneumático. O delineamento experimental adotado foi o em blocos ao acaso, com 05 repetições. As velocidades de semeadura foram de 4; 6; 8; 10 e 12 km h-1. As variáveis avaliadas foram: população de plantas emergidas, distribuição longitudinal e os componentes de rendimento. Aplicou-se a regressão polinomial para os sistemas de disco alveolado horizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 4 publications
2
19
2
16
Order By: Relevance
“…However, in the speed of 7.8 km h -1 the CT management system showed the highest value of pods per plant, but did not differ from the NT system. JASPER et al (2011) found no effect on the yield of soybean components when the sowing speed varied from 4 to 12 km h -1 , which was not verified in this study.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…However, in the speed of 7.8 km h -1 the CT management system showed the highest value of pods per plant, but did not differ from the NT system. JASPER et al (2011) found no effect on the yield of soybean components when the sowing speed varied from 4 to 12 km h -1 , which was not verified in this study.…”
Section: Resultscontrasting
confidence: 87%
“…PEREIRA et al (2011) confirm that for soil management systems (conventional tillage, reduced tillage and no tillage) after five years of cultivation, showed no difference to the stand of soybeans and productivity. JASPER et al (2011) state that the sowing speed (4, 6, 8, 10 and 12 km h-¹) do not affect the plants population, whether for pneumatic doser or horizontal disc, which contradicts this study. The sowing speed influenced the plants stand, being better at the speed of 5.5 km h -1 with 11.91 plants per meter, and the others: 4.6; 7.3 and 7.8 km h -1 with 10.21; 9.58 and 9.83 plants per meter, respectively (Table 4 and Figure 3), which resulted in a quadratic adjust model in the regression.…”
Section: Resultscontrasting
confidence: 85%
“…Liu et al (2004) stated that using fast speeds can compromise the sowing quality. Jasper et al (2011) concluded that faster sowing speeds increased multiples and reduced the acceptable spacing that affected the longitudinal distribution of the seeds for two different seeddispensing systems (pneumatic and horizontal disk honeycomb) and five sowing speeds (1.11, 1.66, 2.22, 2.77 and 3.33 m s -1 ). Mion and Benez (2008) claim that furrow mechanisms are used to ensure seed and fertiliser deposition in the soil and to provide suitable conditions for germination and crop development.…”
Section: Introductionmentioning
confidence: 99%
“…In the precision sowing the feeder mechanism of the seeder has as function the regular dosage of the seeds within the seeding line, with pre-defined spacings (Jasper et al, 2011;Mao et al, 2015;Weirich Neto et al, 2012). Silva & Gamero (2010) state that speed is one of the main factors that interferes with the quality and operational performance during sowing.…”
Section: Introductionmentioning
confidence: 99%